Cutaneous Leishmaniasis Caused by Leishmania Major: A Potential Transmission Hotspot in Senegal – The Case of a 17-Year-Old Girl - Lelo, Souleye; Mhaji, Abdoulkarim; Sylla, Khadime; Gaye, Aissatou; Lam, Ami; Manga, Isaac Akhenaton; Minlekib, Carole Pab; Fall, Cheikh Binetou; Ndiaye, Magatte; Tine, Roger; et al. (European Journal of Applied Sciences, 2026)
Introduction: This is a 13-year-old girl with negative immunological status who was referred to us by the dermatology department at Fann Hospital for a painless ulcerated lesion on her left forearm, which had been developing for three months. Methodology: A serous sample was taken from the lesion for smear and PCR testing. The slides were stained with a 10% Giemsa solution before being read under a microscope with a 100x objective lens. For PCR testing, DNA extraction was first performed using the Quick DNA miniprep Plus kit. Next, nested PCR was performed with the CSBIX-R and CSB2-F primers for the first amplification, and the 13Z and LIR primers for the second amplification. The positive controls used were: Leishmania tropica, Leishmania infantum, and Leishmania major, and water without Rase was used as a negative control. The amplification product was revealed after migration on a 1.5% agarose gel and reading under ultraviolet light. Result: Microscopy revealed amastigote forms of Leishmania, and PCR was used to conclude that the disease was caused by Leishmania major. Conclusion: Leishmaniasis is still present in Senegal with a potential residual transmission focus.